Knowledge management and innovative culture: The examination of Chilean firms across industries - Acevedo, Juan; Díaz-Molina, Iván (Estudios de Administración, 2023)
The article examines the impact of knowledge management on innovative culture across industries with a sample of Chilean workers from larger firms. Through multilevel models, the study confirms that acquisition, dissemination, and responsiveness to knowledge are stronger predictors of innovative culture, comprehending how innovative cultural change could be developed through the routinization of knowledge. Moreover, the critical contribution of this research is to recognize that the relationship between KM and IC has differences across industries. Indeed, service firms have a higher impact on responsiveness to technology, and manufacturing companies are stronger in knowledge acquisition. Dissemination of knowledge is the only dimension with similar behavior among industries